Rational Clinical Pathology Assessment in the Intensive Care Unit. Issue 4 (July 2017) - Rachakonda, K. S.; Parr, M.; Aneman, A.; Bhonagiri, S.; Micallef, S.
Blood tests are ordered on a daily basis in intensive care units (ICU). There are no widely accepted guidelines for testing requirements. This study investigated the impact on ICU laboratory test costs of a multi-strategy change in practice involving routine blood testing. A single centre, prospective, interventional study using historical controls was undertaken to investigate the impact of ICU specialist authorisation of high-volume routine tests on ICU laboratory test costs. Prior to commencement of the study, ICU nursing and junior ICU doctors were able to order tests. During the six-month intervention period, the ICU specialists authorised routine blood tests. Adverse events related to not performing blood tests were also recorded. Overall ICU laboratory test costs decreased by 12.3% over the six months (P=0.0022 versus historical control) with a mean compliance of 51% with the test authorisation protocol. The costs of frequently ordered tests (classified as high-volume) decreased by 20% (P=0.0022 versus historical control). These accounted for an average of 54 ± 3% of the overall ICU blood test costs (blood gas analyses 17%, simple chemistry tests consisting of electrolytes, liver function, calcium, phosphate, magnesium 14%, coagulation 12% and full blood count 11%). Two protocol-related adverse events were recorded and judged as minor and were resolved by ordering tests during the day. No adverse patient outcomes resulted from these two events. Blood testing authorisation by an ICU specialist was associated with significant cost savings in ICU and no adverse patient outcomes.